Liberalization, Financial Instability and Economic Development - Akyüz, Yılmaz (Anthem Press, 2014)
Weighing up the costs and benefits of economic interdependence in a finance-driven world, this book argues that globalization, understood and promoted as absolute freedom for all forms of capital, has been oversold to the Global South, and that the South should be as selective about globalization as the North. 'Liberalization, Financial Instability and Economic Development' challenges the orthodoxy on the link between financial deepening and economic growth, as well as that between the efficiency of financial markets and the benefits of liberalization. Ultimately, the author urges developing countries to control capital flows and asset bubbles, preventing financial fragility and crises, and recommends regional policy options for managing capital flows and exchange rates.